Early and late pace‐maker implantation after transcatheter and surgical aortic valve replacement. Issue 4 (7th August 2020) - Biancari, Fausto; Pykäri, Jouni; Savontaus, Mikko; Laine, Mika; Husso, Annastiina; Virtanen, Marko; Maaranen, Pasi; Niemelä, Matti; Mäkikallio, Timo; Tauriainen, Tuomas; Eskola, Markku; Raivio, Peter; et al.
Abstract: Background: Conduction defects requiring permanent pacemaker (PPM) implantation are frequent complications occurring after surgical (SAVR) and transcatheter aortic valve replacement (TAVR). Methods: Patients who underwent TAVR or SAVR with a bioprosthesis from the nationwide FinnValve registry were the subjects of this study. Patients with prior PPM, who received a sutureless prosthesis, or required cardiac resynchronization therapy or implantable cardioverter defibrillator were excluded from this analysis. Results: Four thousand and ten patients underwent SAVR and 1, 897 underwent TAVR. TAVR had an increased risk of PPM implantation at 30‐day (10.1% vs. 3.5%, unadjusted OR 3.11, 95%CI 2.56–3.87) and 5‐year (15.7% vs. 8.6%, unadjusted SHR, 2.12, 95%CI 1.81–2.48) compared to SAVR. PPM implantation within 30 days from the index procedure did not increase the risk of 5‐year mortality after either SAVR or TAVR. Among 1, 042 propensity score matched pairs, TAVR had an increased risk of PPM implantation at 30‐day (9.9% vs. 4.7%, p < .0001) and 5‐year (14.7% vs. 11.4%, p = .001), but late (>30 days) PPM implantation at 5‐year (4.7% vs. 6.9% SHR 0.72, 95%CI 0.47–1.10) was comparable to SAVR. The types of prosthesis had an impact on 30‐day PPM implantation after TAVR, but not on late (>30 days) PPM implantation. Conclusions: Although the risk of 30‐day PPM implantation is higher after TAVR compared to SAVR, late (>30 days) PPM implantation was comparable with these treatment methods. PPM implantation within 30 days did not affect late survival.